IMPLIKASI GAYA KEPEMIMPINAN DAN SISTEM PENGENDALIAN MANAJEMEN TERHADAP LOYALITAS KARYAWAN DI CV.X BLITAR - Christine Shelley Candrawinata; Sujoko Efferin (CALYPTRA, 2018)
Abstract - This research will discuss about how to improve understanding about the role of leadership style and also management control system to employee loyalty . This study uses the object of a swayalan business located in Blitar.. This research wants to show that the leadership style of a boss and management control system are mutually related to each other and support each other in realizing and creating employee loyalty. If the leadership style is in good shape then it can establish a good management system as well as effective control so that later will provide comfort for employees so as to create employee loyalty will be further increased